Effectiveness Of Aqua Bag Training on Improving Balance Jump Smash of Badminton Athletes - Fajar Arie Mangun; Ari Subarkah; Burhan Basyiruddin (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2026)
Background: Balance is an essential component in executing an effective jump smash in badminton, as it influences body control, landing stability, and stroke accuracy. Innovative training methods are required to enhance athletes’ dynamic balance performance. Aqua bag training, which utilizes unstable water resistance, is considered capable of improving core stability and neuromuscular coordination. However, scientific evidence regarding its effectiveness in improving jump smash balance among badminton athletes remains limited. Therefore, this study aimed to examine the effectiveness of aqua bag training on improving jump smash balance in badminton athletes at Universitas Negeri Jakarta. Research Methodology: This study employed a quantitative experimental method using a pretest–posttest control group design. The participants consisted of badminton athletes from Universitas Negeri Jakarta who were divided into an experimental group receiving aqua bag training and a control group undergoing conventional training. The intervention was conducted for six weeks with a training frequency of three sessions per week. Balance jump smash performance was measured using a dynamic balance test and jump smash performance assessment. Data were analyzed using paired sample t-tests and independent sample t-tests with a significance level of 0.05. Research Results: The results showed a significant improvement in balance jump smash performance in the experimental group after the aqua bag training intervention (p < 0.05). The experimental group demonstrated greater improvement compared to the control group, particularly in landing stability, body balance control, and jump smash execution efficiency. Conclusion: Aqua bag training is effective in improving balance during jump smash performance among badminton athletes. The unstable resistance provided by the aqua bag contributes positively to core stability, coordination, and dynamic balance, making it a recommended training method in badminton conditioning programs.